2023
DOI: 10.1186/s12870-023-04239-2
|View full text |Cite
|
Sign up to set email alerts
|

Population structure analysis to explore genetic diversity and geographical distribution characteristics of wild tea plant in Guizhou Plateau

Abstract: Background Tea, the second largest consumer beverage in the world after water, is widely cultivated in tropical and subtropical areas. However, the effect of environmental factors on the distribution of wild tea plants is unclear. Results A total of 159 wild tea plants were collected from different altitudes and geological types of the Guizhou Plateau. Using the genotyping-by-sequencing method, 98,241 high-quality single nucleotide polymorphisms we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The results of LD analysis showed that the LD of the six subgroups was less than 1 kb, and the LD of ZW was the largest (r 2 = 500 bp), indicating that the selection pressure of these tea plants was low. Compared with Guizhou ancient tea plant (r 2 = 19.3 kb) [27], Guizhou cultivated tea plant (r 2 = 2 kb) [23] and wild tea plant (r 2 = 116 bp) [35], indicating that the selection pressure of Biluochun tea plant population was lower and Biluochun tea plant varieties may have higher genetic diversity. Therefore, they are recommended as materials for studying the evolution, origin, and breeding of tea plants.…”
Section: Population Structure and Genetic Evolution Analysismentioning
confidence: 94%
“…The results of LD analysis showed that the LD of the six subgroups was less than 1 kb, and the LD of ZW was the largest (r 2 = 500 bp), indicating that the selection pressure of these tea plants was low. Compared with Guizhou ancient tea plant (r 2 = 19.3 kb) [27], Guizhou cultivated tea plant (r 2 = 2 kb) [23] and wild tea plant (r 2 = 116 bp) [35], indicating that the selection pressure of Biluochun tea plant population was lower and Biluochun tea plant varieties may have higher genetic diversity. Therefore, they are recommended as materials for studying the evolution, origin, and breeding of tea plants.…”
Section: Population Structure and Genetic Evolution Analysismentioning
confidence: 94%